Distributing trust with the Rampart toolkit - Reiter, Michael (Communications of the ACM, 1996)
Rampart, a toolkit of protocols, was designed to simplify the task of coordinating correctly operating nodes in a dynamic environment characterized by simple and arbitrary node failures, node recoveries and communication failures. Ramapart provides support for distributed process groups, a programming paradigm shown to simplify construction of distributed programs tolerant of simple failures. Rampart supports communication primitives by which group members can multicast messages to the group, and membership primitives by which a process can be removed from or added to the group if it fails or recovers, respectively. Rampart is a research prototype and the subject of ongoing work.